Materialism As Personality: Psychometric Properties Using the Rasch Model - Ririn Mamiek Wulandari; Rahmat Hidayat (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Research on the instrument of materialism as a personality in Indonesia is still lacking. The purpose of this study is to determine the psychometric properties using Rasch model on materialistic personality scale. This study was conducted on 505 diploma/S1/S2 students aged 18-25 years old using accidental sampling technique. Data analysis used the Rasch model which is supported by Winstep software. The results showed there were 16 items that fit with the Rasch model, rating scale functioned appropriately, reliability (item=0,99, person=0,55, Cronbach's Alpha=0,61). The analysis results also showed that there were five items that were gender biased, and very high accuracy of measurement information would be obtained at the moderate materialistic personality level.